Anonymous one-time broadcast using non-interactive dining cryptographer nets with applications to voting - van de Graaf, Jeroen (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2007: Anais do VII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2007.20918, 2007)
All voting protocols proposed so far, with the exception of a few, have the property that the privacy of the ballot is only computational. In this paper we outline a new and conceptually simple approach allowing us to construct a protocol in which the privacy of the ballot is unconditional. Our basic idea is to modify the protocol of Fujioka, Okamoto and Ohta[10], which uses blind signatures so that the voter can obtain a valid ballot. However, instead of using a MIX net, we use a new broadcast protocol for anonymously publishing the vote, a non-interactive variation of the Dining Cryptographer Net.